DEMOCRATIC APPROACH IN ASSESSMENT: A PARADIGM SHIFT IN EXAMINATION REFORM - Hassan, Md. Mozammil; Bharty, Samaresh; Zaidi, Zafar Iqbal (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The assessment system is one of the most important as well as debatable components of our education system. In higher education of India, teaching-learning process is guided by the assessment rather than assessment for teaching-learning. The age old assessment system is also criticized for its rigid and non-democratic nature. This is appropriate for defining our traditional examination system. But the 21st century is very significant in context of examination reforms at all the levels of education. The revolutionary changes in assessment of students introduced many innovative practices. This article analyses the trend of recent examination reforms and conceptualized it as a paradigm shift in assessment ˗ ‘a democratic approach in assessment of students’ progress’. It is democratic in approach, because it ensures the spirit of democracy in assessment based on core democratic values. According National Education Policy-2020, Higher education Institutes (HEIs) shall also move away from high-stakes examinations towards more continuous and comprehensive evaluation. The article redefines the term ‘assessment’ under the democratic approach and explores the democratic values of assessment. This article provides argument in support of democratic approach in assessment for academic excellence.